Embedded metacognitive prompts based on the nature of science: Potentialities, limitations, conditions and possibilities (Research, Society and Development, 2021)
Qualitative research on the possibility of transposition and applicability of the Metacognitive Teaching Strategy (MES) Embedded Metacognitive Prompts Based on Nature of Science. The strategy uses modules with metacognitive commands that direct the study of scientific content based on the nature of science (NDC). The objective was to evaluate the theoretical aspects of primary research, relate them to the description of the steps for its application and evaluate the possibility of its reproduction. We found that NDC, metacognition and self-regulation theories are adequate for protocols and their use in basic education. However, we observed an insufficient explanation for the application of the protocols and the need for articulation between the metacognitive commands, the NDC aspect and the scientific content.